2010
DOI: 10.1002/bit.22918
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Escherichia coli for the production of cadaverine: A five carbon diamine

Abstract: A five carbon linear chain diamine, cadaverine (1,5-diaminopentane), is an important platform chemical having many applications in chemical industry. Bio-based production of cadaverine from renewable feedstock is a promising and sustainable alternative to the petroleum-based chemical synthesis. Here, we report development of a metabolically engineered strain of Escherichia coli that overproduces cadaverine in glucose mineral salts medium. First, cadaverine degradation and utilization pathways were inactivated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 37 publications
2
158
3
2
Order By: Relevance
“…On the basis of the fact that amplification of feedback-resistant lysC showed an increase in lysine production 24 , we constructed WL2 strain to have increased intracellular concentration of lysine compared with WL1. Additional modifications, including overexpression of lysine synthesis pathway and deletion of competing pathways 25 , were made to result in WL3 strain with further increased intracellular concentration of lysine compared with WL2. We confirmed that all the constructed strains showed different intracellular concentrations of lysine as expected ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the fact that amplification of feedback-resistant lysC showed an increase in lysine production 24 , we constructed WL2 strain to have increased intracellular concentration of lysine compared with WL1. Additional modifications, including overexpression of lysine synthesis pathway and deletion of competing pathways 25 , were made to result in WL3 strain with further increased intracellular concentration of lysine compared with WL2. We confirmed that all the constructed strains showed different intracellular concentrations of lysine as expected ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Deamination via transaminase directly yields pyruvate (Gottschalk, 1986) Arginine Be converted to ornithine, which either be used as a hydrogen acceptor or an electron donor or be fermented as a single substrate in Clostridia species (Cunin et al, 1986) Aspartic Acid Be converted to oxaloacetate (Taherzadeh and Karimi, 2008) Cystine Be converted to pyruvate (Taherzadeh and Karimi, 2008) Glutamic Acid Produce amino butyrate-the decarboxylation product of glutamic acid in Clostridia species (Mead, 1971) Glycine Be converted to serine by a reaction involving tetrahydrofolate (Taherzadeh and Karimi, 2008) Histidine Be fermented to the end-products: carbon dioxide, ammonia, and acetic and butyric acids (Pickett, 1943) Isoleucine Be converted to succinyl-CoA (Gottschalk, 1986) Leucine Be converted to 2-oxoisocaproate, then lead to the formation of acetyl-CoA and propionyl-CoA (Gottschalk, 1986) Lysine Degradation of lysine yields cadaverine by decarboxylation (Qian et al, 2011) Methionine Be converted to S-Adenosylmethionine (SAM), which serves as a methyl group donor in various synthetic reaction (Taherzadeh and Karimi, 2008) Phenylalanine Be converted to either phenyl acetic acid or phenyl propionic acid or phenyl lactic acid or phenol or p-cresol or p-hydroxy phenyl acetic acid or p-hydroxy phenyl propionic acid or indole or indole acetic acid or indole propionic acid in Clostridia species (Elsden et al, 1976) Proline Reduction of proline to amino valeric acid in Clostridia species (Mead, 1971) Serine Deaminated to form pyruvate via serine dehydratase (Taherzadeh and Karimi, 2008) Threonine Be converted to pyruvate (Taherzadeh and Karimi, 2008) Tryptophan Be converted to either phenyl acetic acid or phenyl propionic acid or phenyl lactic acid or phenol or p-cresol or p-hydroxy phenyl acetic acid or p-hydroxy phenyl propionic acid or indole or indole acetic acid or indole propionic acid in Clostridia species (Elsden et al, 1976) Tyrosine Be converted to either phenyl acetic acid or phenyl propionic acid or phenyl lactic acid or phenol or p-cresol or p-hydroxy phenyl acetic acid or p-hydroxy phenyl propionic acid or indole or indole acetic acid or indole propionic acid in Clostridia species (Elsden et al, 1976) Valine Be converted to 2-oxoisovalerate, then lead to the formation of acetyl-CoA and propionyl-CoA (Gottschalk, 1986) As shown previously, medium components have a great effect on cell growth and product profiles …”
Section: Critical Factors That Effects Ethanol Productionmentioning
confidence: 99%
“…386 However, to avoid having to produce the (immobilized) enzyme, microbial production from glucose is being pursued using genetically engineered microorganisms such as C. glutamicum 387,388,389 or E. coli. 390 The latter led to a yield on glucose of 0.12 g/g and a production of 9.6 g/L 1,5-diaminopentane with a productivity of 0.32 g (L h) in a fed-batch fermentation. A higher yield, 0.17 g/g, is described using C. glutamicum.…”
Section: 5-diaminopentanementioning
confidence: 98%